Efficacies of rosiglitazone and retinoin on bleomycin-induced pulmonary fibrosis in rats - Yu, Wencheng (Exp Ther Med, 2017)
The present study investigated the intervention efficacies of rosiglitazone (ROS) and retinoin (RET) on bleomycin-induced pulmonary fibrosis in rats. A total of 48 rats were randomly divided into the control group (group C), the model group (group M), the dexamethasone group (group D), the ROS group (group R), the RET group (group W) and the ROS + RET group (group L). Group M and the treatment groups were intratracheally injected with 5 mg/kg bleomycin, while group C was injected with saline. The lungs of rats in each group were inspected using high resolution computed tomography (HRCT), lung tissue hematoxylin and eosin staining and Masson staining; furthermore, lung L-hydroxyproline (Hyp) content and the concentration of transforming growth factor β1 (TGF-β1) serum of each group were also determined. The fibrosis score, Hyp content and TGF-β1 concentration of each treatment group were significantly lower when compared with group M (P<0.01), while the imaging results were improved when compared with group M, with lower alveolitis and fibrosis scores. Group L, R and W exhibited significantly lower fibrosis scores, Hyp content and TGF-β1 concentrations when compared with group D (P<0.05). Imaging results for group L, R and W indicated that while the imaging results were superior to group D, group L was lower than groups R and W (P<0.05). No significant difference in the fibrosis score, Hyp content and TGF-β1 concentration was exhibited between groups R and W (P>0.05). Findings from the present study conclude that ROS and RET are able to suppress bleomycin-induced pulmonary fibrosis with improved efficacies when compared with dexamethasone; furthermore, the combination of these two pharmacological agents may exert synergistic effects.